2017
DOI: 10.1002/celc.201700101
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemiluminescence of Water‐Soluble Poly(amidoamine) Dendrimers Conjugated with Multiple Ru(II) Tris(bipyridine) Moieties

Abstract: Intense electrochemiluminescence (ECL) of water-soluble dendritic conjugates, which are poly(amidoamine) (PAMAM) dendrimers conjugated with multiple Ru(II) tris(bipyridine) ([Ru (bpy) 3 ] 2 + , where bpy = 2,2'-bipyridine) units on the periphery, is demonstrated in the absence of any additional co-reactant. The ECL results were investigated by taking into account the coreactant effect of PAMAM dendrimers. The water-soluble dendritic conjugates were synthesized by derivatizing amine- 2 + -N-hydroxysuccinim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Therefore, the reason can be wellcorrelated with the size, rate of diffusion and high concentration of NPs which affects the excitation of Ru (bpy) 3 2 + and can cause instability in the formation of cation and anion forms of intermediate radicals. For PAMAM dendrimer, the interior tertiary amine groups contributes significantly in enhancing the ECL response rather than its terminal primary or secondary amines [29]. Also, as a general rule it is observed that ECL efficiency increases in the order tertiary > secondary > primary amines [4].…”
Section: Full Papermentioning
confidence: 92%
See 1 more Smart Citation
“…Therefore, the reason can be wellcorrelated with the size, rate of diffusion and high concentration of NPs which affects the excitation of Ru (bpy) 3 2 + and can cause instability in the formation of cation and anion forms of intermediate radicals. For PAMAM dendrimer, the interior tertiary amine groups contributes significantly in enhancing the ECL response rather than its terminal primary or secondary amines [29]. Also, as a general rule it is observed that ECL efficiency increases in the order tertiary > secondary > primary amines [4].…”
Section: Full Papermentioning
confidence: 92%
“…Also, it was found that diamines resulted in much weaker signal than monoamines due to their significant side-reactions [28]. From a study by Lee et al, it was seen that G4À NH 2 dendrimer exhibited highest ECL emission compared to G2 and G6À NH 2 PAMAM dendrimer [29]. Also, Tejeda et al demonstrated that the ECL signal for Ru(bpy) 3 2 + /PAMAM G1.5 dendrimer was higher than G4.5 dendrimer [30].…”
Section: Introductionmentioning
confidence: 99%
“…11 Late in the last century, Richter and Bard pioneeringly reported the ECL properties of a homodinuclear ruthenium complex using 1,4-bis(4′-methyl-2,2′-bipyridin-4-yl)benzene as a bridge ligand, which generated much more intense ECL signals than mononuclear Ru (bpy) 3 2+ . 12 Subsequently, various kinds of skeletons have been designed to construct dinuclear and even multinuclear ruthenium-based ECL luminophores, including dendrimers, [13][14][15][16] dipeptides (lysine-lysine), 17 and widely-used polydentate ligands containing rigid (aromatic) [18][19][20] or flexible (aliphatic hydrocarbon) [21][22][23] bridge linkers. The multi-metallic ruthenium complexes demonstrated unique ECL properties compared with their corresponding mononuclear ruthenium complexes, particularly in the aspects of tuning generated potentials 18 and amplifying signals, 17 among others.…”
Section: Introductionmentioning
confidence: 99%
“…Although there were some differences in the maximum wavelength values between PL and ECL, these differences can be attributed to disparities in the instrument setup and the inner-filter effect. 28,29 Despite these discrepancies, both the PL and ECL spectra exhibited similarities. This indicated that ECL and PL emissions originated from the identical excited state for PL emissions.…”
mentioning
confidence: 99%